Nurse Manager’s Responsibilities in Creating Supportive Working Conditions Post Implementation of Everyday Coping: A Hermeneutic Research Study of District Nurses’ Experiences - Marianne Hauan; Kari Kvigne; Johanne Alteren (Nursing Research and Practice)
Aim. To gain knowledge about how district nurses experience changes in working conditions and discuss nursing manager’s responsibility in facilitating working conditions for district nurses following the implementation of everyday coping. Background. To overcome the challenges related to the sustainability of the healthcare sector, everyday coping was implemented in district nursing. The implementation was set by the government and implemented by the municipality. The nursing manager has an overall responsibility to facilitate working conditions so that everyday coping can be applied into district nursing practice. Method. This descriptive and interpretative study involved 19 interviews and 19 observations on 10 nurses. Kvale and Brinkmann’s three levels of understanding were employed in the analysis. Results. Three categories were established based on the results of the data analyses: (i) time and space are not considered, (ii) crossfire of conflicting expectations, and (iii) nursing manager’s commitment to everyday coping. Conclusion. The working conditions of district nurses are not adapted for them to work according to the everyday coping mindset. The nursing manager has a key role in supporting nurses and addressing challenges the nurses meet in their daily work, where everyday coping is implemented. The study highlights the importance for healthcare managers, at various levels in the healthcare sector, to be conscious of the district nursing practice, its complexity, and quality of health services when implementing change. This knowledge is important when planning future healthcare and nursing practice.